DMO online platforms: Image and intention to visit. (April 2018) - Molinillo, Sebastian; Liébana-Cabanillas, Francisco; Anaya-Sánchez, Rafael; Buhalis, Dimitrios
Abstract: The online platforms (i.e., websites and social media) of Destination Management Organizations (DMOs) are among the most useful tools for building and promoting a destination image (DI). However, the associated effects on the DI have not been sufficiently studied and prior research has not assessed the influences of involvement on the DI formation process. The aim of this study is to explore the moderating effects of DMO online platforms on the DI through a conceptual model. The proposed model was empirically verified through an experiment and tested using PLS-SEM method. The findings demonstrate that tourist involvement has a positive impact on cognitive image and affective image, forming the DI as an antecedent of the intention to visit. The results also show that image formation and intention to visit the destination vary depending on the platform used by travelers to access the information. Highlights: DMO websites and social media moderate destination image and intention to visit. Tourist involvement has a positive impact on cognitive image and affective image. Cognitive image and affective image lead to overall destination image. Cognitive image plays a more important role, especially in social media. These relationships have been confirmed through Facebook and Instagram models.